Public house and beverage management : key principles and issues - Flynn, Michael; Ritchie, Caroline; Roberts, Andrew, 1953-; ScienceDirect eBooks (Oxford : Butterworth-Heinemann, 2000)
'Public House & Beverage Management' provides students with a practical guide to the management aspects of the licensed trade industry. 'Public House & Beverage Management' introduces students to: * Key players * Variations in service offer * Types of management arrangement (managed, leased, tenanted, franchise, freehouse) * Customers and segments * Labour markets and employees * Key elements in the business units * Retailing skills. The combined experiences of the authors are reflected in the text, as between them they have a vast range of experience as: publican, hotelier, chef and sommelier. Enhanced by this is their teaching and research covering food service, cellar management, marketing and wines and spirit education. Covers the management aspects of the licensed trade industry Progresses from a simple definition through to the management of each function to conclude with the strategic view of both companies and the industry Has a full set of pedagogic features including chapter summaries/objectives, real-life case studies, review and reflect questions and further reading and references.
A history of the licensed trade industry; The modern industry; The licensed enterprise and the law; The marketing function; Management of the products and services; Managing the human resources; Controlling your profits; Ethics and dilemmas: the challenges of the licensed trade industry; Careers and contacts.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Bars (Drinking establishments) -- Management; BUSINESS & ECONOMICS -- Industries -- Hospitality, Travel & Tourism; TRAVEL -- Restaurants; Bars (Drinking establishments) -- Management; Electronic books